Nightmare of a pathologist: Metastatic adenocarcinoma from breast to gastrointestinal system and gallbladder (Annals of Medical Research, 2022)
Aim: Breast tumors usually metastasize to lymph nodes, bone, lung, liver and central nervous system, and rarely to gastrointestinal system (GIS) and gallbladder. In this study, we aimed to present and discuss our breast carcinoma cases with GIS and gallbladder metastases. Material and Methods: Clinicopathological findings of nine breast tumors with metastases to gallbladder and GIS were evaluated in our study. Results: The mean age was 51.2 years. Seven cases, five of which were invasive ductal carcinoma (IDC) and two invasive lobular carcinoma (ILC), had metastases to GIS. In these cases, metastatic foci were mostly observed in stomach, small intestine, sigmoid colon and rectum, respectively. The diagnosis of two cases with metastases to gallbladder was IDC. In two cases, one with gastric and other, with gallbladder metastases, lymph nodes were also involved. All cases died aside from an IDC with gallbladder metastasis and an ILC with gastric metastasis. Conclusion: Metastasis from a breast tumor should be taken into consideration particularly in cases with unknown primary. GIS and gallbladder, though rare, might be the metastatic foci of breast carcinomas.
Keywords: Breast; gallbladder; gastrointestinal system; metastasis